2008
DOI: 10.1590/s1413-86702008000100004
|View full text |Cite
|
Sign up to set email alerts
|

Auditory disorders and acquisition of the ability to localize sound in children born to HIV-positive mothers

Abstract: The objective of the present study was to evaluate children born to HIV-infected mothers and to determine whether such children present auditory disorders or poor acquisition of the ability to localize sound. The population studied included 143 children (82 males and 61 females), ranging in age from one month to 30 months. The children were divided into three groups according to the classification system devised in 1994 by the Centers for Disease Control and Prevention: infected; seroreverted; and exposed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 23 publications
2
31
1
1
Order By: Relevance
“…The fact that the ART groups did not differ in measures of peripheral hearing ability (DPOAEs, thresholds), or in the rate of abnormal tympanograms, but that the ART+ group reported significant more trouble understanding speech and had higher gap detection thresholds point to a reduction in central processing abilities as a cause of the findings. These data are consistent with findings from other studies showing longer ABR latencies in HIV+ adults, and difficulty in localizing sound in infants born to HIV+ mothers (Pagano, Cahn et al 1992; Bankaitis and Keith 1995; Castello, Baroni et al 1998; Matas, Leite et al 2006; Matas, Iorio et al 2008). …”
Section: Discussionsupporting
confidence: 92%
“…The fact that the ART groups did not differ in measures of peripheral hearing ability (DPOAEs, thresholds), or in the rate of abnormal tympanograms, but that the ART+ group reported significant more trouble understanding speech and had higher gap detection thresholds point to a reduction in central processing abilities as a cause of the findings. These data are consistent with findings from other studies showing longer ABR latencies in HIV+ adults, and difficulty in localizing sound in infants born to HIV+ mothers (Pagano, Cahn et al 1992; Bankaitis and Keith 1995; Castello, Baroni et al 1998; Matas, Leite et al 2006; Matas, Iorio et al 2008). …”
Section: Discussionsupporting
confidence: 92%
“…Other studies have reported a higher prevalence of hearing loss among children living with HIV than our estimates [14,17], potentially because the participants in our study were generally healthier, for instance with a low proportion of patients with WHO Stage III/IV. Furthermore, the BCOE is a tertiary health center with more resources than most health centers in Malawi, including equipment for testing hearing (e.g.…”
Section: Discussioncontrasting
confidence: 58%
“…Predominant types of hearing loss in HIV-infected children have varied across studies, with several studies reporting the majority with conductive hearing loss [10,16], as in this study, while others studies reported higher prevalence of sensorineural hearing loss [8,9,15] or central auditory disorders [14]. The high prevalence of conductive hearing loss in this and other studies was likely due to high rates of ear infections, as we saw high rates of middle ear abnormalities, such as perforated tympanic membranes.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…26 The study method included DPOAE testing in two or three steps, and immittance and BAEP tests (see Fig. 1).…”
Section: Discussionmentioning
confidence: 99%